Mouse Yolk Sac Hematopoiesis - Yamane, Toshiyuki (Frontiers in Cell and Developmental Biology, 2018)
The yolk sac is the first observed site of hematopoiesis during mouse ontogeny. Primitive erythroid cells are the most well-recognized cell lineages produced from this tissue. In addition to primitive erythroid cells, several types of hematopoietic cells are present, including multipotent hematopoietic progenitors. Yolk sac-derived blood cells constitute a transient wave of embryonic and fetal hematopoiesis. However, recent studies have demonstrated that some macrophage and B cell lineages derived from the early yolk sac may persist to adulthood. This review discusses the cellular basis of mouse yolk sac hematopoiesis and its contributions to embryonic and adult hematopoietic systems.